Adsorption properties of silica with covalently bound 8-hydroxyquinoline with respect to toxic metal ions - Glushchenko, O.V.; Yanovska, E.S.; Kichkiruk, O.Yu.; Tertykh, V.A. (Functional Materials, 2006)
Conditions of a single-stage chemical Ьinding of 8-hydroxyquinoline molecules to the
surface of inorganic matrix using of the Mannich aminomethylation reaction and adsorption properties of so obtained chemically modified silica with respect to ions of toxic metals have been studied. The synthetic method provides a high concentration and a homogeneous distribution of complexing groups over the surface, and the adsorbent obtained displays a high capacity to some environmentally toxic metals (>2 mmol/g) and satisfactory adsorption kinetic properties, thus making it possible to use the adsorbent for the ion preconcentration both in static and dynamic modes. The structure studies of toxic metal complexes with 8-hydroxyquinoline immobilized at silica surface by ESR and IR spectroscopy testify that the metal ions are co-ordinated with bound ligand through nitrogen and oxygen atoms. Дослiджено умови одностадiйного методу хiмiчного закрiплення молекул 8-оксихiнолiну шляхом здiйснення у поверхневому шарi неорганiчної матрицi реакцiї амiнометилування Маннiха та адсорбцiйнi властивостi одержаного хiмiчно модифiкованого кремнезему щодо iонiв токсичних металiв. Метод синтезу забезпечує рiвномiрний розподiл та високу концентрацiю комплексоутворюючих груп на поверхнi, а одержаний сорбент виявляе високу сорбцiйну ємнiсть вiдносно до бiльшостi токсичних металiв (>2 ммоль/г) та хорошi кiнетичнi характеристики, що дозволяє використовувати адсорбент для передконцентрування iонiв як у статичному, так i у динамiчному режимi. Дослiдження будови комплексiв токсичних металiв з iмобiлiзованим на поверхнi кремнезему 8-оксихiнолiном методами ЕПР та IЧ-спектроскопiї свiдчать про координацiю iонiв металiв iз закрiпленим лiгандом через атоми нiтрогену i оксигену. Исследованы условия одностадийного метода химического закрепления молекул 8-оксихинолина путем осуществления в поверхностном слое неорганической матрицы реакции аминометилирования Манниха и адсорбционные свойства полученного химически модифицированного кремнезёма по отношению к ионам токсичных металлов. Метод синтеза обеспечивает равномерное распределение и высокую концентрацию комплексообразующих групп на поверхности, а полученный сорбент имеет высокую сорбционную емкость по отношению к большинству токсичных металлов (>2 ммоль/г) и хорошие кинетические характеристики, что позволяет использовать адсорбент для предконцентрирования ионов как в статическом, так и в динамическом режиме. Исследования строения комплексов токсичных металлов с иммобилизованным на поверхности кремнезема 8-оксихинолином методами ЭПР и ИК-спектроскопии свидетельствуют о координации ионов металлов с закрепленным лигандом через атомы азота и кислорода.